Public understanding of climate change and support for mitigation - Shane Timmons; Pete Lunn (The Economic and Social Research Institute (ESRI), 2022)
In this study, a large, representative sample of the Irish population undertook a multiple-choice quiz about climate change. The 10-minute quiz was designed to engage participants and to measure their understanding, not of facts and figures, but of the scientific relationships behind climate change - of what causes what, and how. The study was conducted in mid-October 2021. As well as revealing how well the population understands climate change, the central focus of the study was the relationship between understanding and willingness to act. To investigate this, the study contained an experiment that tested whether exposing people to the answers to the quiz questions altered their attitudes to climate policy and individual behaviour. Half the sample was randomly assigned to see the answers to the quiz questions, while the other half was not.We then measured support for climate mitigation policy (in particular, a carbon tax) and judgements of individual behaviour. In this way, we conducted an experimental test of whether engaging with accurate scientific information about climate change has an impact on willingness to tackle it.
Keywords: 330; Klimapolitik; Klimaschutz; Öffentliche Meinung; Irland